Sex differences in disordered eating and food addiction among college students. (1st October 2018) - Yu, Zhiping; Indelicato, Natalie Arce; Fuglestad, Paul; Tan, Michael; Bane, Lindsay; Stice, Caitlin
Abstract: This cross-sectional study aimed to assess sex differences and weight status differences in disordered eating behaviors (DEB) and food addiction (FA) along with their co-occurrence among college students. Self-reported demographic and weight information, the Eating Attitude Test (EAT-26), and Yale Food Addiction Scale (YFAS) were collected from 965 college students. Participants included 703 (72.8%) female, 720 (74.8%) white, and ranged in age from 18 to 25 years old. Female college students had a significantly higher prevalence of DEB (11.6% vs. 5.7%, p  = 0.007, odds ratio ( OR ) = 2.19) and higher prevalence of FA (12.3% vs. 4.6%, p  < 0.0001, OR  = 3.04) than male students. The co-occurrence was also significantly higher in female students than in male students (5.4% vs. 1.9%, p  = 0.022, OR  = 3.03). Male and female obese participants versus healthy weight participants had higher prevalence of DEB (15.1% vs.8.6%, p  = 0.047, OR  = 1.91) and FA (19.4% vs. 8.9%, p  = 0.002, OR  = 2.51). Higher prevalence of DEB was positively associated with FA regardless of sex and weight status. The findings indicate higher prevalence of disordered eating in female college students than male students and add to the research on sex differences in food addiction. The co-occurrence of both and association between high prevalence of DEB and FA warrant additional research on the incidence as well as factors that contribute to sex differences. Understanding sex differences and comorbidity regarding DEB and FA is critical for the prevention and treatment of eating related disorders.